ANALISIS EFEKTIVITAS PENGGUNAAN MATERIAL DINDING PADA PEMBANGUNAN GEDUNG BERTINGKAT - Mananoma, Tiny; Sela, Reynaldo Jeremy; The, Femmy (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
The development of science, especially in the field of construction, has produced various innovations, one of which is on wall materials that can support the effectiveness of work, especially in the construction of multi-storey buildings. It is realized that wall material can affect acoustic, thermal, and visual comfort levels. The choice of wall material has a direct impact on the environment where the use of environmentally friendly materials can reduce carbon footprint and construction waste. This study aims to analyze the effectiveness of the use of wall materials such as red brick, adobe and lightweight brick in terms of structural strength, cost and service life of the structure. To compare various alternatives, an assessment of each alternative consequence is carried out using a decision-making system. The results of the analysis showed that alternative 3 using lightweight brick obtained the highest value so that alternative 3 became the top priority of other alternatives to optimize the construction of high-rise buildings.